IS COAL ABLE TO SHINE? THE ROLE OF LEGAM IN SUPPORTING COAL JEWELRY-BASED SOCIAL ENTREPRENEURSHIP - Rakhman Priyatmoko; Addin Maulana; Dini Oktaviyanti; Yessy Febrina Usman; Fauziah Khoiriyani (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2024)
As coal mining activities ceased in Sawahlunto, tourism, and the creative industry emerged as alternative avenues for the city's development. Legam is a player in the creative industry, specifically in the fashion sub-sector, specializing in coal-based jewelry production, a material abundant in Sawahlunto. Employing a narrative approach and conducting interview data collection, this research aimed to identify the role of Legam Jewelry in supporting social entrepreneurship. A social entrepreneurship approach served as the analytical framework, considering Legam Jewelry's unique business operations. Differences in the locations of raw material sources, workers' residences, and the business owner's domicile increased operational costs. It was interesting to comprehend Legam's motivation for maintaining this location difference between Bandung and Sawahlunto. The research findings indicated that Legam aligned its business processes with social entrepreneurship elements such as social value, civil society, innovation, and economic activities. Despite being deemed capable of fulfilling these social entrepreneurship elements, several critical points required attention in Legam's business processes. One such point related to the need for government support to facilitate physical exhibitions after the coronavirus disease (COVID-19) pandemic. In creating a massive social impact, efforts were necessary to encourage the emergence of similar entrepreneurs in Sawahlunto and other regions.